The Spirodela polyrhiza genome reveals insights into its neotenous reduction fast growth and aquatic lifestyle - Wang, Wenqin; Haberer, G.; Gundlach, H.; Gläßer, Christine; Nussbaumer, T.; Luo, M. C.; Lomsadze, A.; Borodovsky, M.; Kerstetter, Ra*; Shanklin, J.; Byrant, D. W.; Mockler, T. C.; et al. (Nature Communications, 2014)
The subfamily of the Lemnoideae belongs to a different order than other monocotyledonous species that have been sequenced and comprises aquatic plants that grow rapidly on the water surface. Here we select Spirodela polyrhiza for whole-genome sequencing. We show that Spirodela has a genome with no signs of recent retrotranspositions but signatures of two ancient whole-genome duplications, possibly 95 million years ago (mya), older than those in Arabidopsis and rice. Its genome has only 19,623 predicted protein-coding genes, which is 28% less than the dicotyledonous Arabidopsis thaliana and 50% less than monocotyledonous rice. We propose that at least in part, the neotenous reduction of these aquatic plants is based on readjusted copy numbers of promoters and repressors of the juvenile-to-adult transition. The Spirodela genome, along with its unique biology and physiology, will stimulate new insights into environmental adaptation, ecology, evolution and plant development, and will be instrumental for future bioenergy applications.